DETERMINATION OF THE BIOLOGICAL PROPERTIES OF PATHOGENS OF THE TRICHOPHYTON RUBRUM STRAIN ISOLATED FROM THE HUMAN BODY - Zhumayev, B. K.; Shapekova, N. L.; Zhumayeva, А. K.; Cukhar, Е. В. (Наука и образование №4, 2020)
научный журнал -- отечественное издание -- периодическое издание -- журнал кксон -- онихомикоза -- дерматит -- кожные болезни -- изоляты -- ветеринария -- pathogens of dermatomycosis -- mycelium -- nutrient medium -- dermatomycetes
Keywords: научный журнал; отечественное издание; периодическое издание; журнал кксон; онихомикоза; дерматит; кожные болезни; изоляты; ветеринария; pathogens of dermatomycosis; mycelium; nutrient medium; dermatomycetes